2009
DOI: 10.1016/j.physa.2008.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Information and flux in a feedback controlled Brownian ratchet

Abstract: We study a feedback control version of the flashing Brownian ratchet, in which the application of the flashing potential depends on the state of the particles to be controlled. Taking the view that the ratchet acts as a Maxwell's demon, we study the relationship that exists between the performance of the demon as a rectifier of random motion and the amount of information gathered by the demon through measurements. In the context of a simple measurement model, we derive analytic expressions for the flux induced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 25 publications
2
63
0
Order By: Relevance
“…Still, there is no complete theoretical framework detailing the relationship between feedback and thermodynamics. Interest in developing such a framework -a thermodynamics of feedback -has grown recently in part due to experiments on feedback cooling [3,4] and feedback control of nanoparticles [5,6]; experimental, computational, and theoretical studies of feedback driven Brownian ratchets [7][8][9][10][11][12]; and new theoretical predictions relating dissipation to information [13][14][15][16][17][18][19][20][21][22][23].Recently, Sagawa and Ueda derived a generalization of the second law of thermodynamics for quantum and classical systems manipulated by one feedback loop [18,19], which subsequently has been verified experimentally [24] and extended to classical systems driven by repeated discrete feedback -implemented through a series of feedback loops initiated at predetermined times -independently by Horowitz and Vaikuntanathan [20], and Fujitani and Suzuki [21]. The second law of thermodynamics for discrete feedback states that the average work dissipated W d in driving a system with a discrete feedback protocol from one equilibrium state at inverse temperature β to another at the same temperature is related to the microscopic information gained through measurements I by…”
mentioning
confidence: 99%
“…Still, there is no complete theoretical framework detailing the relationship between feedback and thermodynamics. Interest in developing such a framework -a thermodynamics of feedback -has grown recently in part due to experiments on feedback cooling [3,4] and feedback control of nanoparticles [5,6]; experimental, computational, and theoretical studies of feedback driven Brownian ratchets [7][8][9][10][11][12]; and new theoretical predictions relating dissipation to information [13][14][15][16][17][18][19][20][21][22][23].Recently, Sagawa and Ueda derived a generalization of the second law of thermodynamics for quantum and classical systems manipulated by one feedback loop [18,19], which subsequently has been verified experimentally [24] and extended to classical systems driven by repeated discrete feedback -implemented through a series of feedback loops initiated at predetermined times -independently by Horowitz and Vaikuntanathan [20], and Fujitani and Suzuki [21]. The second law of thermodynamics for discrete feedback states that the average work dissipated W d in driving a system with a discrete feedback protocol from one equilibrium state at inverse temperature β to another at the same temperature is related to the microscopic information gained through measurements I by…”
mentioning
confidence: 99%
“…For big enough potential heights, V 0 k B T , the stopping force is F stop 3 4 V 0 , whereas for small potential heights, V 0 k B T , it is F stop 1 4 V 0 . In both limiting cases, the stopping force is proportional to V 0 , as found in the continuous case [11,12]. We can also look for the force F * that maximizes the mean power P = J (1) s F at fixed V 0 .…”
Section: Dynamics: Flux Of Particlesmentioning
confidence: 90%
“…In addition, flux and power performance have been studied as a function of the amount of information used by the controller [11,12]. In this paper, we address the computation of the efficiency of a feedback flashing ratchet as an application of the recent results on the thermodynamics of feedback-controlled systems presented in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…However, for these later systems no systematic study on the role of information has been performed. On the other hand, for feedback flashing ratchets, relations between the information I (about the system) gathered by the controller per step and the performance have been recently obtained [38,39]. These relations have been established for a collective feedback flashing ratchet compounded of one or few particles, considering the optimal protocol for one particle and its generalization to few particles.…”
Section: Feedback Controlled Ratchets and Informationmentioning
confidence: 99%
“…The computations in [38] have shown that the maximum increase in the flux that can be obtained has an upper bound proportional to the square root of the information I received in each step, i.e.,…”
Section: Feedback Controlled Ratchets and Informationmentioning
confidence: 99%